Sensus communis and Critical Judgment in Eighteenth-Century Theories of Taste - Gatti, Andrea (Diciottesimo Secolo, 2025)
The debate surrounding the concept of common sense played a significant role in shaping the major currents of thought and society in 18th-century England. Initially regarded as synonymous with widespread, and sometimes fallacious, opinions, the concept gained epistemological validity during the century’s second half. This shift occurred after the rejection of common sense had led to the development of theories that hindered further intellectual progress, standing in stark contrast to the epistemological insights that would later be considered incontrovertible. This essay examines the nature and effects of the peculiar notion of common sense that emerged in this period, both in theoretical and practical terms, as well as within individual and social contexts. The study aims to analyze the implications and effects of sensus communis as it evolved during this time and investigates the role it plays in articulating certain speculative tendencies underlying eighteenth-century aesthetic inquiries in England.